Mixed‐Halide Perovskites with Suppressed Phase Segregation for Large Modulation Depth and High‐Stability Terahertz Modulators - Xunjun He; Binchao Sun; Guangjun Lu; Zhaoxin Geng; Ying Zhang (Small Structures)
Metal‐halide perovskites with tunable bandgaps are promising semiconductors in heterojunction engineering for high‐performance terahertz modulators. However, most traditional perovskite‐based terahertz modulators reported so far are difficult to simultaneously achieve both large modulation depth and high environmental stability in a simple structure. To overcome this bottleneck, herein, the Cs0.25MA0.75PbI2Br/MAPbI3/Si dual‐heterojunction terahertz modulator is fabricated using two‐step spin‐coating method. In this device, the Cs0.25MA0.75PbI2Br film formed by substituting Br− at the X‐site and Cs+ at the A‐site from MAPbI3 can not only tailor the bandgaps but also suppress the phase segregation, while the MAPbI3 film can promote the accumulation of photon‐generated electrons in the Si substrate. Moreover, the maximum modulation depth of the fabricated THz modulator is 71% at 0.42 THz. Compared to the Cs0.25MA0.75PbI2Br/Si or MAPbI3/Si samples, the modulation depth can be increased by almost 100%. After continuous operation in an environment with 70% humidity for 10 h, the device can still operate stably. This study illuminates the potential for high‐performance perovskite‐based devices, as well as offers new strategies to improve the stability of perovskites.